Resource Mobilization for HCFC Phase-out and Climate Mitigation Co-benefits : A Study Prepared for the Executive Committee of the Multilateral Fund - World Bank (Washington, DC, 2015)
This study seeks to identify potential sources of co-financing to meet the additional costs of energy efficiency (EE) and climate mitigation benefits associated with the hydrochlorofluorocarbons (HCFC) phase-out supported by the Multilateral fund of the montreal protocol (MLF). As it stands, the policy of the multilateral fund is to support only the eligible incremental costs related to the phase-out of ozone depleting substances, and not to support the additional costs of additional EE related improvements of the equipment. Currently therefore, while the multilateral fund encourages exploring co-financing opportunities for improving energy efficiency, the fund does not directly support the uptake of the most energy efficient technology. HCFC phase-out management plans (HPMPs) approved by the MLF seek to facilitate the conversion of refrigeration - air conditioning (Ref-AC) manufacturing and foam manufacturing away from the use of HCFCs to non - ozone depleting substance (ODS) alternatives. This study explores pathways that may encourage the uptake of ozone- and climate friendly technologies through synergies between the MP, policies to promote EE, and climate finance instruments; thereby leading also to cost-effectiveness of public financing and economic efficiency where synergies exist and can be exploited. The study underscores, based on practical examples, that opportunities can be strategically engineered to encourage harmonization between the phase-out of the HCFCs and HCFC-using technologies with efforts to promote energy efficiency and reduce greenhouse gas emissions (GHG).